2014
DOI: 10.9790/0661-16110111
|View full text |Cite
|
Sign up to set email alerts
|

An Extended Approach for Online Testing of Reversible Circuits

Abstract: Reversible computing has tremendous benefits in terms of power consumption, less heat dissipation and packaging density. Because its applications are found in diverse fields including quantum computing, nanotechnology, low power CMOS designs and cryptography, Reversible computing has gained attraction of many researchers recently. In order to incorporate fault testing capability in reversible circuits, a number of offline and online approaches have been proposed. In order to extend online testability of revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In [7,8], parity preserving technique is used for online testing of circuits consisting of only k-CNOT gates or only Peres gate. But here we have shown that by replacing each gate by its parity preserving extended gate and following the steps given below any circuit consisting of any combination of basic reversible gates can be tested.…”
Section: G Proposed Methods For Single Stuck At Fault Online Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…In [7,8], parity preserving technique is used for online testing of circuits consisting of only k-CNOT gates or only Peres gate. But here we have shown that by replacing each gate by its parity preserving extended gate and following the steps given below any circuit consisting of any combination of basic reversible gates can be tested.…”
Section: G Proposed Methods For Single Stuck At Fault Online Testingmentioning
confidence: 99%
“…They have explained how other approaches are unnecessarily high in overhead when compared to their proposed newapproach. So, in testing our memory array we have adopted extended gates method.This paper [7] extends an existing online testing approach [8] by proposing a testable substitution of the Peres gate.…”
Section: F Online Testing and Related Workmentioning
confidence: 99%
See 1 more Smart Citation